Fatores de risco associados à mastite bovina causada por Prototheca zopfii - Yamamura, Aline Artioli Machado; Müller, Ernst Eckhardt; Freire, Roberta Lemos; Freitas, Júlio César de; Pretto-Giordano, Lucienne Garcia; Toledo, Roberta dos Santos; Ribeiro, Márcio Garcia [UNESP] (Universidade Federal de Santa Maria (UFSM), 2008)
Este trabalho teve como objetivo o estudo de fatores de risco associados à mastite bovina causada por Prototheca zopfii. Foram analisadas 13 propriedades leiteiras dos Estados do Paraná e de São Paulo, segundo os seguintes critérios de seleção: confirmação prévia de casos de mastite por Prototheca spp., triagem pela pesquisa de Prototheca spp. em tanques de expansão e latões e rebanhos com contagem de células somáticas acima de 5x105cel mL-1. As amostras coletadas consistiram de: leite, água, solo, fezes e swab de teteiras. Prototheca spp. foi isolada de amostras de leite dos quartos mamários com mastite clínica ou subclínica em uma propriedade e de amostras de leite e do ambiente em quatro propriedades, nas quais foi isolada em amostras de: água de bebedouro, abastecimento, esgoto, empoçada no piso de estábulo e sala de ordenha, solo de piquete e pasto, teteiras, fezes de bezerros e suínos. do total de 383 vacas examinadas, Prototheca spp. foi isolada em 20 (5,2%) vacas, sendo caracterizada como P. zopfii em 18. Os fatores de risco associados à mastite causada por P. zopfii foram: criação das vacas a pasto, alimentação dos animais com pasto e silagem, realização de ordenha mecânica em estábulo, permanência das vacas após ordenha em piquete sem alimento, criação de suínos próxima às instalações dos bovinos, existência de cães, gatos e roedores, falta de higienização dos tetos com água, pré-imersão dos tetos em aplicador com retorno e sem a troca do anti-séptico, alimentação dos bezerros com leite de vacas com mastite clínica e serem as vacas da raça holandesa.

This research had as objective the study of risk factors associated with bovine mastitis caused by Prototheca zopfii. Thirteen dairy herds in Paraná and São Paulo states were analyzed and selected according to the following criteria: previous confirmation of Prototheca spp. mastitis cases, screening of Prototheca spp. in bulk tanks and milk cans, and herds with somatic cells count over 5x105cel mL-1. The samples collected consisted of: milk, water, soil, manure and swabs of teat cup rubbers. Prototheca spp. was isolated from mammary quarters with clinical and subclinical mastitis of milk samples in one herd and from the environment and cows in four herds. Out of 383 cows examined, Prototheca spp. was isolated in 20 (5.2%) cows with mastitis, and 18 of them were characterized as P. zopfii. In four herds when Prototheca spp. was identified from mammary quarters and environment the agent was isolated from the following samples: water in the waterers, puddled water in the stalls and the milking parlour, supply, sewage, cow pen and pasture soil, teat cup rubbers and manure from calves and swines. The risk factors associated with P. zopfii mastitis consisted of: pasture system, pasture and silage feeding, use of milking machine in stalls, cow pen without fresh feed after milking, raising of swines near bovine housing, existence of dogs, cats and rodents, absence of teats hygienization with water, use of pre-immersion devices with return and without change of antiseptic, calves fed with milk of clinical mastitis cases and the Holstein breed.
Risk factors associated with bovine mastitis caused by Prototheca zopfii
Keywords: mastite bovina; bovinos leiteiros; alga; Prototheca spp; bovine mastitis; dairy cattle; algae; Prototheca spp